Kết quả nghiên cứu xói lở bờ Sông Hồng khu vực Thành phố Lào Cai - Túc, Nguyễn Đăng; Hướng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
SummaryStudy results on the Red River bank erosion in the area of Lao Cai cityThe paper introduces study results on current erosion state of the Red River banks and erosioncausing factors in the area of Lao Cai city. Erosion along the Red River has occurred drastically in recent years, erosion rate is up to 10 m/year nearby a school at Van Hoa commune. Geomorphology, geology and hydro-litho dynamics are the main factorcausing erosion along the river.Studying on factors of geomorphology and geology shows that geometry and structure of river banks including materials, geotechnical setting, groundwater levels, heights and slopes of river banks, as well asactive tectonic faults are the most favorable factors for river bank erosion.Hydro-litho dynamic factors such as : high angle of river bed, dired channels to river banks are major causes to intensify erosion. Flow velocities in both dry and rainy seasons are very high, causing continuous erosion at both sides of the Red River.